Upcycled Products in Indonesia: Factors Influencing Willingness to Pay - Parung, Christabel Annora Paramita; Viviany, Viviany (Keluwih: Jurnal Sains dan Teknologi, 2022)
Abstract—Research on clothes waste reduction, especially upcycling suggests that solutions aimed at reducing clothing waste are effective. Based on this ground, further research on upcycling is carried out. As Indonesian millennials can be categorized as ecologically conscious consumers nowadays, it is possible that upcycling can grow more rapidly and become the solution to the world-waste problem. To make that happen, further research needs to be done to increase public and fashion business owners’ awareness. This research examines the willingness to pay for upcycled products in Indonesia. The method of this research is a mixed method - qualitative and quantitative method, which was conducted through online surveys of 30 participants and 5 people in a forum group discussion to gain deeper information. Data were analyzed using van Westendorp’s analysis of price sensitivity. The finding of this research is that the consumers are willing to pay 3-4 times more expensive than the original garment price as the ideal price of upcycled products, the factors influencing it are meaningfulness, familiarity with sustainable products, and quality improvement of the products. Keywords: upcycle, willingness to pay, fashion, sustainable fashion Abstrak—Penelitian tentang pengurangan limbah pakaian, khususnya upcycling, menunjukkan bahwa solusi yang ditujukan untuk mengurangi limbah pakaian cukup efektif. Berdasarkan hal tersebut, penelitian tentang upcyling banyak dilakukan. Dengan melihat peluang bahwa milenial Indonesia saat ini dapat dikategorikan sebagai konsumen yang sadar lingkungan, maka tidak menutup kemungkinan bahwa upcycling dapat berkembang lebih pesat dari sekarang untuk dapat menjadi solusi dari permasalahan sampah dunia. . Untuk mewujudkannya, perlu dilakukan penelitian lebih lanjut untuk meningkatkan kesadaran masyarakat dan pemilik bisnis fashion. Penelitian ini mengkaji tentang kesediaan membayar (WTP) produk hasil upcycling di Indonesia. Metode penelitian ini adalah metode kualitatif dan kuantitatif, menggunakan kuesioner yang diberikan kepada 30 orang, dan FGD meliputi 5 orang, dengan analisis sensitivitas harga milik van Westendorp. Temuan dari penelitian ini adalah konsumen bersedia membayar 3-4 kali lebih mahal dari harga garmen asli sebagai harga ideal produk upcycled, dan faktor-faktor yang memengaruhinya adalah kebermaknaan, keakraban dengan produk yang berkelanjutan, dan peningkatan kualitas produk. Kata kunci: upcycle, fesyen, fesyen berkelanjutan, kesediaan membayar